1992
DOI: 10.1021/j100193a040
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation kinetics and infrared spectra of the complexation of lithium ion by triethylene glycol and by tetraethylene glycol in acetonitrile

Abstract: Ultrasonic absorption relaxation spectra are reported covering the frequency range -1-500 MHz for the complexation of LiC104 by the open-chain polyethers triethylene glycol (EG3) and tetraethylene glycol (EG4) in acetonitrile at 25 OC and at a molar ratio R = [EG3]/[LiC104J or R = [EG4]/[LiCI04] = 1. The ultrasonic spectra can be described by the sum of two Debye relaxation processes which were interpreted according to the Eigen-Winkler mechanism Li+ + EG Li' ... EG Li+EG (LPEG) k-1 k-i(where EG denotes either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…Solutions of LiCF 3 SO 3 in acetonitrile (CH 3 CN) have also been studied. 10,37 Our measurements for this system at room temperature show bands at 1300 cm -1 (33%), 1272 cm -1 (32%), and 1255 cm -1 (27%) which are in agreement with those of Lindgren and co-workers 10 and Cobranchi et al 37 Irish and co-workers [49][50][51] have studied the asymmetric stretch region of the nitrate anion. The ν 3 (E′) degenerate mode for NO 3occurs at ∼1300 cm -1 .…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Solutions of LiCF 3 SO 3 in acetonitrile (CH 3 CN) have also been studied. 10,37 Our measurements for this system at room temperature show bands at 1300 cm -1 (33%), 1272 cm -1 (32%), and 1255 cm -1 (27%) which are in agreement with those of Lindgren and co-workers 10 and Cobranchi et al 37 Irish and co-workers [49][50][51] have studied the asymmetric stretch region of the nitrate anion. The ν 3 (E′) degenerate mode for NO 3occurs at ∼1300 cm -1 .…”
Section: Resultssupporting
confidence: 82%
“…The bands at 1299 and 1255 cm -1 have been attributed to contact-ion pairs, , , where interactions in the solution have lifted the degeneracy of the doubly degenerate SO 3 asymmetric stretch. Solutions of LiCF 3 SO 3 in acetonitrile (CH 3 CN) have also been studied. , Our measurements for this system at room temperature show bands at 1300 cm -1 (33%), 1272 cm -1 (32%), and 1255 cm -1 (27%) which are in agreement with those of Lindgren and co-workers 10 and Cobranchi et al 8 Infrared spectra of the SO 3 asymmetric stretch region shown for lithium and sodium triflate electrolytes. …”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations